1995
DOI: 10.1074/jbc.270.13.7420
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory Cytokines and Environmental Stress Cause p38 Mitogen-activated Protein Kinase Activation by Dual Phosphorylation on Tyrosine and Threonine

Abstract: Protein kinases activated by dual phosphorylation on Tyr and Thr (MAP kinases) can be grouped into two major classes: ERK and JNK. The ERK group regulates multiple targets in response to growth factors via a Ras-dependent mechanism. In contrast, JNK activates the transcription factor c-Jun in response to pro-inflammatory cytokines and exposure of cells to several forms of environmental stress. Recently, a novel mammalian protein kinase (p38) that shares sequence similarity with mitogen-activated protein (MAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
1,549
11
15

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,094 publications
(1,645 citation statements)
references
References 50 publications
70
1,549
11
15
Order By: Relevance
“…Another member of the mitogen-activated protein kinase (MAPK) family, p38, was ®rst identi®ed as a protein that is phosphorylated at a tyrosine residue upon treatment of murine pre-B cells with lipopolysaccharide (LPS) (Han et al, 1993). Further studies have shown that p38 is activated in response to hyperosmolarity and mediators of inflammation, such as interleukin-1 (IL-1) and tumor necrosis factor a (TNF-a) (Han et al, 1994;Raingeaud et al, 1995). Both JNK and p38 are activated during apoptosis that is induced by various environmental stresses, such as heat shock, osmotic stress and UV light (Xia et al, 1995;Raingeaud et al, 1995;Galcheva-Gargova et al, 1994;Kyriakis and Avruch, 1996).…”
Section: Of Results From Three Independent Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another member of the mitogen-activated protein kinase (MAPK) family, p38, was ®rst identi®ed as a protein that is phosphorylated at a tyrosine residue upon treatment of murine pre-B cells with lipopolysaccharide (LPS) (Han et al, 1993). Further studies have shown that p38 is activated in response to hyperosmolarity and mediators of inflammation, such as interleukin-1 (IL-1) and tumor necrosis factor a (TNF-a) (Han et al, 1994;Raingeaud et al, 1995). Both JNK and p38 are activated during apoptosis that is induced by various environmental stresses, such as heat shock, osmotic stress and UV light (Xia et al, 1995;Raingeaud et al, 1995;Galcheva-Gargova et al, 1994;Kyriakis and Avruch, 1996).…”
Section: Of Results From Three Independent Experimentsmentioning
confidence: 99%
“…Further studies have shown that p38 is activated in response to hyperosmolarity and mediators of inflammation, such as interleukin-1 (IL-1) and tumor necrosis factor a (TNF-a) (Han et al, 1994;Raingeaud et al, 1995). Both JNK and p38 are activated during apoptosis that is induced by various environmental stresses, such as heat shock, osmotic stress and UV light (Xia et al, 1995;Raingeaud et al, 1995;Galcheva-Gargova et al, 1994;Kyriakis and Avruch, 1996). The withdrawal of NGF from cultures of PC12 cells leads to activation of JNK and p38 and inhibition of ERK (Xia et al, 1995).…”
Section: Of Results From Three Independent Experimentsmentioning
confidence: 99%
“…Many transcription factors encompassing a broad range of action have been shown to be phosphorylated and subsequently activated by p38. Examples include activating transcription factor 1, 2 & 6 (ATF-1/2/6), SRF accessory protein (Sap1), CHOP (growth arrest and DNA damage inducible gene 153, or GADD153), p53, C/EBPβ, myocyte enhance factor 2C (MEF2C), MEF2A, MITF1, DDIT3, ELK1, NFAT, and high mobility group-box protein 1 (HBP1) [17,55,[66][67][68][69][70][71][72][73][74][75][76]] . An important cis-element, AP-1 appears to be influenced by p38 through several different mechanisms.…”
Section: Transcription Factors Activated By P38mentioning
confidence: 99%
“…We also analysed the phosphorylation pro®les of another member of the MAPK family, p38, which was recently found to be activated transiently in response to EPO (Nagata et al, 1997). Activation of p38 is known to occur through phosphorylation of threonine-180 and tyrosine-182 (Raingeaud et al, 1995), and this can also be monitored by similar immunoblot assay. In the ras17N-expressing cells, however, only gradual decrease in the levels of total p38 protein as well as its phosphorylated form was observed ( Figure 4b).…”
Section: Oncogenementioning
confidence: 99%